Comparison of Prevalence of Diabetes Mellitus, Medical Expenses, Inpatient, Emergency and Outpatient According to the Level of Physical Activity of Korean Adults: A Cross-Sectional Study - Byung Kun Lee (Asian Society of Kinesiology, 2019)
OBJECTIVES The purpose of this paper is to analyze the differences in the prevalence of diabetes mellitus, in relation to the physical activity grade and to compare differences in, personal medical expenses, the days of hospitalization, inpatient, outpatient and emergency. METHODS The medical panel data of Korea used in 2016, with a total of 13,523 adults and 1,404 diabetes mellitus patients. Physical activity level measured with IPAQ questionnaire, and displayed as MET-minutes per week. The days of hospitalization, personal medical expenses, using of inpatient, outpatient and emergency investigated, and frequency analysis, logistic regression, ANOVA, and Chi-square performed. RESULTS The prevalence of diabetes mellitus based on inactive group was reduced both minimally active group (odds ratio [OR] = 0.81) and active group (OR = 0.73, p<.01). The personal medical expenses I(p<.05) and II(p<.01) were all significantly different among each physical activities group. Medical expenses have increased by 33.3~35.1 % in minimally active group compared with active group, while inactive groups have increased rapidly by 58.8~65.6 %. There were significant differences in inpatient and emergency using depend on the level of physical activity. CONCLUSIONS The SEI could provide a relative evaluation of jumping performance depending on physical resources without consideration of physique.